2013
DOI: 10.1017/s1355617713000301
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse Inhibition in HIV-Associated Neurocognitive Disorders

Abstract: Sensorimotor inhibition, or the ability to filter out excessive or irrelevant information, theoretically supports a variety of higher-level cognitive functions. Impaired inhibition may be associated with increased impulsive and risky behavior in everyday life. Individuals infected with HIV frequently show impairment on tests of neurocognitive function, but sensorimotor inhibition in this population has not been studied and may be a contributor to the profile of HIV-associated Neurocognitive Disorders (HAND). 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 60 publications
5
42
0
Order By: Relevance
“…In the present study, although we were not powered to examine sex differences, we have found that even with mixed sex groups, gp120 alters PPI. These data are also consistent with a report examining PPI in HIV-infected individuals, which found significant PPI impairments in HIV+ individuals with HAND, as compared to HIV+ individuals without HAND (Minassian et al, 2013). This finding further underscores the relevance of the gp120 mouse model as a tool for examining the neurobiology and neuropathology of HIV infection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, although we were not powered to examine sex differences, we have found that even with mixed sex groups, gp120 alters PPI. These data are also consistent with a report examining PPI in HIV-infected individuals, which found significant PPI impairments in HIV+ individuals with HAND, as compared to HIV+ individuals without HAND (Minassian et al, 2013). This finding further underscores the relevance of the gp120 mouse model as a tool for examining the neurobiology and neuropathology of HIV infection.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, HAND subjects demonstrate severe PPI compared to HIV+ individuals with no cognitive alterations (Minassian et al, 2013). In this study, we have attempted to provide the biological basis for the mechanisms underlying this anxiety-induced neuronal plasticity, and we have observed a significant increase in dendrite spines in the BLA of gp120tg mice, associated with an anxiety-like behavior.…”
Section: Discussionmentioning
confidence: 99%
“…PPI can be assessed across species. Impaired sensorimotor inhibition, measured by PPI of the eyeblink startle response, was observed in HIV-infected persons with neurocognitive impairment (in the domain of working memory in particular) compared to cognitively intact HIV-infected persons (Minassian et al 2013), suggesting that early inhibition deficits accompany or may even precede downstream cognitive impairment in HIV-infected individuals.…”
Section: Neurobehavioral Disturbancementioning
confidence: 99%
“…PPI deficits have also been reported in gp120 transgenic mice, although these impairments appear to differ between males and females (Henry 2014). Interestingly, a recent study demonstrated PPI deficits in HIV-positive individuals with a diagnosis of HAND, but not in cognitively asymptomatic HIV-positive participants (Minassian 2013). These results, together with the fact that the PPI is reduced following treatment with dopaminergic agonists such as amphetamines, suggest that alterations in PPI may be caused by viral protein-induced changes in the dopaminergic system of the HIV-1Tg rat (Moran, Booze et al 2013).…”
Section: Behavioral Alterations In the Hiv-1tg Ratmentioning
confidence: 99%